ANALYSIS OF THE EFFECT OF WORK MOTIVATION, WORK ENVIRONMENT, AND WORK STRESS ON EMPLOYEE PERFORMANCE AT PT BANK TABUNGAN NEGARA (BTN) SHARIA SEMARANG BRANCH OFFICE - Dwi Eri Fitriyani; Muhammad Asrori; Saniman Widodo (Applied Accounting and Management Review (AAMAR), 2022)
This study aims to analyze the significance of the effect of work motivation, work environment, and work stress on employee performance at PT Bank Tabungan Negara (BTN) Sharia Semarang Branch Office either simultaneously or partially. The population in this study were all employees at PT Bank Tabungan Negara (BTN) Sharia Semarang Branch Office. The sampling technique used was purposive sampling, as many as 55 employees. The data used in this study is primary data obtained through the distribution of questionnaires. The data analysis model uses multiple linear regression analysis model. While the data analysis technique used the F statistical test, the coefficient of determination (R2 ), and the t statistic test which was processed using the SPSS 26 program. The results of the analysis and discussion show that work motivation, work environment, and work stress simultaneously have a significant effect on employee performance at PT Bank Tabungan Negara (BTN) Sharia Semarang Branch Office. Partially, work motivation has a positive and significant effect. Meanwhile, work environment and work stress have a positive and insignificant effect on employee performance at PT Bank Tabungan Negara (BTN) Sharia Semarang Branch Office.